Varieties of American English ( Teacher's handbook ) - Preston, Dennis R. (United States Department of State, 1988)
This handbook is intended to supplement the three-part videocassette series varieties of American English, which consists of regional dialects; social and specialized groups and strylistic differences. The series is available on 16-mm film as well as in its original videotape form.